OPTIMALISASI SUMBER DANA PENDIDIKAN DI SDIT: KOLABORASI ANTARA ORANGTUA, YAYASAN, DAN KOMITE SEKOLAH - Suryaningtiyas Puspa Wardhani; Rezki Gunawan; Siti Nurjanah; Subandi; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the strategy of optimizing educational funding sources in Islamic Integrated Elementary Schools (SDIT) through effective collaboration among three key stakeholders: parents, school foundation, and school committee. Financial limitations often hinder SDIT from maintaining educational quality and implementing various enrichment programs. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis in several SDIT across region Natar Lampung Selatan. The findings indicate that synergy among parents as primary contributors, foundations as institutional managers, and school committees as community representatives significantly enhances financial sustainability. Transparent budgeting, participatory planning, and innovative funding programs such as productive waqf, school cooperatives, and fundraising events emerged as effective models. The study recommends strengthening communication among stakeholders and improving financial management capacity based on Islamic financial principles to ensure long-term sustainability of educational funding in SDIT.